Since Time Immemorial Native Custom and Law in Colonial Mexico - Yannakakis, Yanna (Duke University Press, 2023)
Yanna Yannakakis traces the creation of Indigenous custom as a legal category and its deployment as a strategy of resistance to empire in colonial Mexico.